Influence of stabilization treatment on low cycle fatigue behavior of Ti alloy IMI 834 - Kumar A.; Singh N.; Singh V. (My University, 2025)
Low cycle fatigue (LCF) behavior of the near-α titanium alloy Ti-6Al-4Sn-4Zr-0.70Nb-0.50Mo-0.40Si (IMI 834) was studied at three total strain amplitudes (±0.8%, ±1%, and ±1.25%) at room temperature in both unstabilized and stabilized conditions. Specimens were solution treated in the (α+β) phase field at 1020 °C and quenched in water or cooled in air. The solution-treated specimens were stabilized by aging at 700 °C for 2 h, followed by cooling in air. Cyclic softening was exhibited both by the unstabilized and the stabilized specimens at all three strain amplitudes. However, the degree of softening was relatively greater in the stabilized specimens. The LCF life of the stabilized specimens was found to be much lower than that of the unstabilized specimen. This is attributed to the detrimental influence of the Ti3Al precipitates present in the stabilized specimens. © 2004 Elsevier Inc. All rights reserved.